A comprehensive review on the pre-research of nanofluids in absorption refrigeration systems. (November 2022) - Jiang, Weixue; Song, Jinwei; Jia, Tao; Yang, Liu; Li, Shuhong; Li, Yanjun; Du, Kai
Abstract: Due to the shortage of primary energy, absorption refrigeration system (ARS) has received more and more attention because they can effectively use low-grade energy. However, compared with vapor compression refrigeration system (VCRS), ARS has lower efficiency and it is difficult to miniaturize. Therefore, ARS has been restricted to a certain extent in terms of development. But fortunately, more and more efforts have been made to improve the performance of ARS, especially based on nanofluids to improve heat and mass transfer efficiency. In this paper, the pre-research of nanofluids discussed in ARS are mainly divided into preparation process and stability analysis, thermo-physical properties and heat transfer performance, absorption and generation process, and the influence of nanoparticles on the whole ARS, etc. The aim of this investigation is to identify the research gaps and present promising approach for future study and reveal which type and the corresponding concentration of nanofluid mostly improve the performance of each part of the system. Conclusions and some suggestions for future scope are also presented that would encourage the real application of nanofluids and improve the coefficient of performance (COP) of ARS as soon as possible.